Environmental impact assessment framework for product packaging. Issue 3 (9th April 2018) - Singh, Sumer; Kumar, Jyoti; Rao, P.V.M.
Abstract : Purpose: The purpose of this paper is to investigate and propose a framework for environmental impact assessment of packaging material being used to package a product. Design/methodology/approach: The research considers parameters identified in the literature by the use of "Delphi Technique". Based on available data, methods of measurement of the parameters are carried out. Furthermore, a metrics is proposed for measurement of environmental impact. Based on the metrics, the research proposes a framework for environmental impact assessment by use of Dominic's method. The research validates the proposed framework through Pahl and Beitz method. Findings: The proposed framework establishes a metrics for measurement of 16 parameters for environmental impact assessment. The framework can be used to compare a set of alternate packaging material for the same product for its environmental impact. The framework also provides a quantitative measure of the environmental impact assessment of a product packaging. Research limitations/implications: The research can be used to evaluate a packaging as compared to its alternate. It can also be used to propose suggestions for improving the environmental impact of packaging in comparison to its alternate. Practical implications: The data considered for establishing of metrics for measurement of parameters for environmental impact may not be available in all practical situations in the similar way as considered in the research. Originality/value: This paper proposes a framework for environmental impact assessment for product packaging considering data in the Indian scenario.